2011
DOI: 10.1111/j.1460-9592.2011.03554.x
|View full text |Cite
|
Sign up to set email alerts
|

Crossover comparison of airway sealing pressures of 1.5 and 2 size LMA‐ProSeal™ and LMA‐Classic™ in children, measured with the manometric stability test

Abstract: The LMA-ProSeal™ and LMA-Classic™ size 1.5 and 2 provide similar mean airway sealing pressures as assessed by the manometric stability test under standardized conditions, with similar air leak and optimal positioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 14 publications
4
13
0
Order By: Relevance
“…In adults, the rate of successful gastric tube placement correlates with correct positioning of the LMA ProSeal and LMA Supreme (14). Overall gastric tube placement was 100% in our study with LMA ProSeal same with the previous data published before (5,12,13). This rate was 97% for LMA Supreme and it is comparable the previous data too (1)(2)(3).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In adults, the rate of successful gastric tube placement correlates with correct positioning of the LMA ProSeal and LMA Supreme (14). Overall gastric tube placement was 100% in our study with LMA ProSeal same with the previous data published before (5,12,13). This rate was 97% for LMA Supreme and it is comparable the previous data too (1)(2)(3).…”
Section: Discussionsupporting
confidence: 92%
“…These rates were even higher than neuromuscutar blockade receiving and spontaneously breathing children with LMA ProSeal (10)(11)(12). The studies comparing the LMA Supreme in spontaneously breathing and neuromuscular receiving children did not detect any gastric insufflation in any patient (1)(2)(3).…”
Section: Discussionmentioning
confidence: 84%
“…Other studies have also reported similar incidence. [1314] Though i-gel inserts less pressure on perilaryngeal tissue because of its noninflatable cuff, the incidence of sore throat was comparable in all three groups. This observation of our study is supported by the study of Wong et al .…”
Section: Discussionmentioning
confidence: 99%
“…In that study the success rate for inserting the device was 80% on the first attempt and 100% after two attempts. [1213] Other studies of using the pediatric i-gel[14] and LMAs[1516] have shown similar results. The ease of insertion was graded as ‘easy’ or ‘very easy’ in all cases in the i-gel group and 90% (27 of 30) in the PLMA groups.…”
Section: Discussionmentioning
confidence: 78%
“…Other studies have also reported a similar incidence. [1415] Although i-gel inserts less pressure on the perilaryngeal tissue because of its non-inflatable cuff, the incidence of sore throat is comparable in the two groups. This observation in our study is supported by the study of Seet et al .…”
Section: Discussionmentioning
confidence: 99%